Therapeutic Potential of Pharmacological Targeting NLRP3 Inflammasome Complex in Cancer - Tezcan, Gulcin; Garanina, Ekaterina E.; Alsaadi, Mohammad; Gilazieva, Zarema E.; Martinova, Ekaterina V.; Markelova, Maria I.; Arkhipova, Svetlana S.; Hamza, Shaimaa; McIntyre, Alan; Rizvanov, Albert A.; Khaiboullina, Svetlana F. (Frontiers in Immunology, 2021)
Introduction Dysregulation of NLRP3 inflammasome complex formation can promote chronic inflammation by increased release of IL-1β. However, the effect of NLRP3 complex formation on tumor progression remains controversial. Therefore, we sought to determine the effect of NLRP3 modulation on the growth of the different types of cancer cells, derived from lung, breast, and prostate cancers as well as neuroblastoma and glioblastoma in-vitro. Method The effect of Caspase 1 inhibitor (VX765) and combination of LPS/Nigericin on NLRP3 inflammasome activity was analyzed in A549 (lung cancer), MCF-7 (breast cancer), PC3 (prostate cancer), SH-SY5Y (neuroblastoma), and U138MG (glioblastoma) cells. Human fibroblasts were used as control cells. The effect of VX765 and LPS/Nigericin on NLRP3 expression was analyzed using western blot, while IL-1β and IL-18 secretion was detected by ELISA. Tumor cell viability and progression were determined using Annexin V, cell proliferation assay, LDH assay, sphere formation assay, transmission electron microscopy, and a multiplex cytokine assay. Also, angiogenesis was investigated by a tube formation assay. VEGF and MMPs secretion were detected by ELISA and a multiplex assay, respectively. Statistical analysis was done using one-way ANOVA with Tukey’s analyses and Kruskal–Wallis one-way analysis of variance. Results LPS/Nigericin increased NRLP3 protein expression as well as IL-1β and IL-18 secretion in PC3 and U138MG cells compared to A549, MCF7, SH-SY5Y cells, and fibroblasts. In contrast, MIF expression was commonly found upregulated in A549, PC3, SH-SY5Y, and U138MG cells and fibroblasts after Nigericin treatment. Nigericin and a combination of LPS/Nigericin decreased the cell viability and proliferation. Also, LPS/Nigericin significantly increased tumorsphere size in PC3 and U138MG cells. In contrast, the sphere size was reduced in MCF7 and SH-SY5Y cells treated with LPS/Nigericin, while no effect was detected in A549 cells. VX765 increased secretion of CCL24 in A549, MCF7, PC3, and fibroblasts as well as CCL11 and CCL26 in SH-SY5Y cells. Also, VX765 significantly increased the production of VEGF and MMPs and stimulated angiogenesis in all tumor cell lines. Discussion Our data suggest that NLRP3 activation using Nigericin could be a novel therapeutic approach to control the growth of tumors producing a low level of IL-1β and IL-18.